IN 1924 HOW WAS THE FIRST ISSUE OF THE “ERKIN TOO” NEWSPAPER PUBLISHED? (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The analysis of the first historical issue of the newspaper Erkin Too, published in the Kyrgyz language, provides insight into the emergence of Kyrgyz journalism. The study of its content, articles, the reasons for their writing, and the reflection of events of that time offers an understanding of the formation process of the printing industry in Kyrgyzstan.
Keywords: Research, newspaper, Arabic script, Latin alphabet, 1924, Decree, V.I. Lenin, publishing industry, class struggle, poor, Great October Revolution, freedom.